Establishment and characterization of a fin cell line from Takifugu obscurus and its application to fish immunology - Jie Wang; Jingping Zhang; Shuang Han; Youquan Wang; Liangbiao Chen (Journal of Fish Biology, 2025)
Takifugu obscurus (pufferfish) is an important species in aquaculture and has become widely popular in China and Japan. However, the development of the pufferfish aquaculture industry has been significantly impacted by severe diseases. Fish cell lines, as a model for in vitro studies, have the advantages of low cost, easy culture, and low genetic variation rate. A novel cell line from the fin of T. obscurus was established in this study and named TOF. TOF grew optimally with L‐15 medium at 28°C and showed a multipolar fibroblast‐like morphology. Mitochondrial cytochrome oxidase subunit 1 ( COI ) gene identification and karyotype detection confirmed that TOF cells originated from T. obscurus and the chromosome number was 44 (2 n = 44). Transfection experiments showed that TOF cells were able to transfect and express exogenous genes by lipofection and electroporation. The studies of salinity (NaCl) and alkalinity (NaHCO 3 ) on TOF proliferation showed that the highest multiplication rate of TOF was obtained at 6‰ NaCl mass and 4 g/L alkalinity, respectively. Furthermore, the expressions of several genes associated with the immune response were significantly upregulated after stimulating TOF cells with lipopolysaccharide (LPS) and poly (I:C), including irf7 , il10 , myd88 , and nod1 . Additionally, the Aeromonas hydrophila infection assay with TOF cells showed that TOF cells were sensitive to bacteria, and pufferfish could promote antimicrobial activity through NLR/NF‐κB pathway to regulate the production of cytokines. This study suggested that TOF cell line could be an advantageous in vitro model for the investigation of fish immunology and virology, and could assist us to better comprehend the T. obscurus immune response to bacterial invasion.